Use of ganciclovir in the therapeutic approach to feline herpetic keratitis: Case report - Guimarães, Tarcísio Guerra; Cardoso, Karla Menezes; Mamede, Fabricio Villela; Alexandre, Nuno (Pubvet, 2024)
Feline herpesvirus-1 (FHV-1) infection is widely prevalent in cats and can manifest through a variety of ocular clinical signs. Once infected, the feline will be a latent carrier for life, and recurrent clinical episodes of the virus may occur. The therapeutic approach depends on the stage of infection and the severity of the disease. The main elements of treatment are antiviral therapy, antibiotic therapy and supportive treatment. The antiviral ganciclovir in ophthalmic formulation is available for humans. However, there are anecdotal reports of its use in infected cats. Thus, our objective was to report a therapeutic approach with topical ganciclovir on the eye of a cat with FHV-1. The ophthalmic formulation of ganciclovir was shown to be well tolerated and effective in the ocular treatment of a cat with FHV-1.